Arsenic perception and signaling: The yet unexplored world - Navarro, Cristina; Navarro, Micaela A.; Leyva, Antonio (Frontiers in Plant Science, 2022)
Arsenic is one of the most potent carcinogens in the biosphere, jeopardizing the health of millions of people due to its entrance into the human food chain through arsenic-contaminated waters and staple crops, particularly rice. Although the mechanisms of arsenic sensing are widely known in yeast and bacteria, scientific evidence concerning arsenic sensors or components of early arsenic signaling in plants is still in its infancy. However, in recent years, we have gained understanding of the mechanisms involved in arsenic uptake and detoxification in different plant species and started to get insights on arsenic perception and signaling, which allows us to glimpse the possibility to design effective strategies to prevent arsenic accumulation in edible crops or to increase plant arsenic extraction for phytoremediation purposes. In this context, it has been recently described a mechanism according to which arsenite, the reduced form of arsenic, regulates the arsenate/phosphate transporter, consistent with the idea that arsenite functions as a selective signal that coordinates arsenate uptake with detoxification mechanisms. Additionally, several transcriptional and post-translational regulators, miRNAs and phytohormones involved in arsenic signaling and tolerance have been identified. On the other hand, studies concerning the developmental programs triggered to adapt root architecture in order to cope with arsenic toxicity are just starting to be disclosed. In this review, we compile and analyze the latest advances towards understanding how plants perceive arsenic and coordinate its acquisition with detoxification mechanisms and root developmental programs.